Retrospective evaluation of acid–base imbalances, clinicopathologic alterations, and prognostic factors in hospitalized calves with Eimeria-associated diarrhea - Urgibl-Bauer, Andrea; Lorch, Annette; Badura, Dana; Zablotski, Yury; Constable, Peter D.; Trefz, Florian M. (Frontiers in Veterinary Science, 2025)
IntroductionAfter the neonatal period Eimeriosis is one of the most common causes of large intestinal diarrhea in calves. In contrast to neonatal calves with diarrhea, there are very few reports about the clinicopathological alterations in affected animals, which are mainly based on experimental data. The aim of the present study was therefore to characterize acid–base and related clinicopathologic alterations in calves with Eimeria-associated diarrhea and to identify variables associated with in-hospital mortality.MethodsRetrospective analysis of clinical and clinicopathologic findings extracted from medical records of 118 calves aged 1 to 5 months admitted to a veterinary teaching hospital.ResultsSeverely affected calves were profoundly hyponatremic and hypochloremic, with a strong correlation between plasma sodium and chloride concentrations (Spearman’s rs = 0.90). Acidemia was found in 57.6% of calves and was associated with hyperphosphatemia, hyper-L-lactatemia, and the presence of unidentified strong ions. Forty-seven calves (39.8%) did not survive to hospital discharge. Classification tree analysis indicated that hospital mortality was associated with plasma ionized calcium concentrations <1.05 mmol/L, initial leukocyte counts >16 × 109 cells/L, and a poor or cachectic body condition. The resulting sensitivity and specificity for predicting non-survival of this model was 59.6 and 90.1%, respectively. In addition to plasma ionized calcium [Odds ratio (OR) = 0.011] and leukocyte concentrations (OR = 1.08), recumbency (OR = 6.1), albumin (OR = 0.90), and decreased strong ion difference (OR = 0.91) were associated with mortality in a second modeling approach (sensitivity 78.7%, specificity 71.8%).ConclusionCalves with Eimeria-associated diarrhea can develop profound clinicopathologic derangements. The identified prognostic factors suggest that advanced disease severity, indicated by an inability to stand and reduced body condition, is associated with a lower chance of survival.